Maternal age at birth shapes offspring life-history trajectory across generations in long-lived Asian elephants - Sophie Reichert; Vérane Berger; John Jackson; Simon N. Chapman; Win Htut; Khyne U. Mar; Virpi Lummaa (Blackwell Scientific Publications Ltd., 2022)
1. Advanced maternal age at birth can have pronounced consequences for offspring health, survival and reproduction. If carried over to the next generation, such fitness effects could have important implications for population dynamics and the evolution of ageing, but these remain poorly understood. While many laboratory studies have investigated maternal age effects, relatively few studies have been conducted in natural populations, and they usually only present a "snapshot" of an offspring's lifetime. 2.In the present study, we focus on how maternal age influences offspring life-history trajectories and performance in a long-lived mammal. 3.We use a multigenerational demographic dataset of semi-captive Asian elephants to investigate maternal age effects on several offspring life-history traits: condition, reproductive success, and overall survival. 4.We show that offspring born to older mothers display reduced overall survival but higher reproductive success, and reduced survival of their own progeny. Our results show evidence of a persistent effect of maternal age on fitness across generations in a long-lived mammal. 5.By highlighting transgenerational effects on the fitness of the next generation associated with maternal age, the present study helps increase our understanding of factors contributing to individual variation in ageing rates and fitness.